Gemfibrozil-trans-cinnamic acid co-crystal: Synthesis, characterization, in vitro solubility and cell viability studies - Jéssica Ribeiro Alves Silva, Bruno Barreto da Cunha Holanda, Gabriela Trindade de Souza e Silva, Carla Roberta Peachazepi Moraes, Thúlio Wliandon Lemos Barbosa, Érica Mendes dos Santos, Erich V. De Paula, Renan Marcel Bonilha Dezena, Halima Samsodien,Paulo César Pires Rosa (Journal of Applied Pharmaceutical Science, 2023)
The co-crystallization is a technic used to improve drug properties, mainly for drugs belonging to classes II and IV of the Biopharmaceutical Classification System like gemfibrozil (GEM). This study aims to synthesize a new co-crystal of GEM and trans-cinnamic acid (TCA) through the mechanochemistry method, characterize it using powder X-ray diffraction, Fourier-transform infrared spectroscopy, differential scanning calorimetry, and thermogravimetric analysis, and determine the equilibrium solubility and cytotoxicity of the new crystalline form. The characterization techniques indicated that the cocrystal was successfully formed, especially because they revealed a unique X-ray pattern and a single endothermic event, different from the isolated substances. The concomitant use of GEM and TCA was shown to be safe at concentrations up to 100 M in models using Caco-2 cells. The formation of the GEM: TCA co-crystal was successful, and the new co-crystal was not cytotoxic at the concentrations analyzed.
Keywords: Gemfibrozil, co-crystal, liquid assisted grinding (LAG), powder X-ray diffraction (PXRD), Fourier-transform infrar